تأثير فعالية الإشراف الجماعي على دوافع تعلم طلاب الفصل الثاني بالمدرسة المتوسطة الحكومية الأولى بمانتينجان نجاوى جاوى الشرقية إندونيسيا - Heru Saiful Anwar (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
School counseling services are provided to help or to solve problems of students. Problems that experienced by students can affect the concentration and decrease the spirit of student’s in learning activities. SMP N 1 Mantingan is one of the state schools located in Sambirejo-Mantingan-Ngawi which uses group guidance program in improving the spirit of learning of their students. This study aims to determine the effectiveness of group guidance on improving student learning motivation. This research used quantitative approach, data was obtained by questionnaire method and data used in mean formula to get mean value and formula of contingency coefficient correlation to find influence between them. The population of this study is students of SMPN 1 Mantingan-Ngawi-East Java with the number 254. And the sample taken for research is 25% of the total students of class II, it is 64 students. From this research, it can be concluded that (1) the effectiveness of group guidance on students' motivation of second grade SMP Negeri 1 Mantingan has 41,97 and span 41-51 (2) level of learning motivation of second grade SMP Negeri 1 Mantingan has a value of 52, 84 and is in a range of 49-63 (3) the influence of effectiveness of group guidance on student learning motivation of second grade SMP Negeri 1 Mantingan- Ngawi -Jawa Timur- Indonesia academic year 2015-2016. With correlation index 0,338 after compare with table r product moment with df 62 data at 5% significance level = 0,245 hence relation obtained is weak relation, because is in the range 0,21-0,40.